Optimizing the role of health cadres in dental and oral health based on primary service integration - Fatkhurrohman, Fuad; Arimbi, Arimbi (Universitas Muhammadiyah Magelang, 2025)
Oral and dental health is a reflection of a community's quality of life. However, the incidence of oral and dental diseases remains high. Therefore, the prevention of these diseases requires cross-sectoral collaboration by optimizing the role of health cadres. The objective of this community service program was to enhance cadres' knowledge of oral and dental health and their social support for early detection of oral and dental diseases. The implementation method involved a training program for 10 health cadres from Petaranga Village who are concerned with oral and dental health. The training utilized lectures, discussions, demonstrations, and practical sessions. Post-program evaluation results showed a significant increase in the health cadres' knowledge and skills regarding oral and dental health, as well as the social support they can provide to individuals with these diseases. Quantitatively, the average knowledge score increased from 70 to 90, which was statistically significant (p=0.000), proving the effectiveness of the primary service integration-based training program.